KEBERDAYAAN PETANI DALAM PEMASARAN BAHAN OLAHAN KARET RAKYAT (BOKAR) DI KECAMATAN GUNUNG TOAR DAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Lita Arfah; Rosnita Rosnita; Novia Dewi (Indonesian Journal of Agricultural Economics, 2019)
This research aims to: 1) identify market mechanism of auctions and conventional markets in Kuantan Mudik and Gunung Toar district of Kuantan Singingi regency, 2) analyze the empowerment of rubber farmers auction marketing system and conventional. Research was conducted in district of Kuantan Mudik precisely in the Pebaun Hilir and Sangau village then in Gunung Toar district at Gunung village and Lubuk Terentang village. Population in this study were farmers who use the auction system and marketing of conventional systems calculated by Slovin formula. The samples were 146 from auction system and 158 for conventional systems. Research results showed that the marketing mechanism of auction system followed by rubber farmers (sellers), traders (buyers), extension officers and organizers of the auction market,  it is held once in a week and the buyer who offers the highest price of bokar will win the auction. The conventional system of marketing can be done every day and prices of rubber (bokar) established by the traders (the buyer). The farmers who adopt the auction systems show empowerment with an average score of 2,96, while farmers who adopt the conventional system of marketing is in a position of unempowerment with the average score 2,15.